Par1b links lumen polarity with LGN–NuMA positioning for distinct epithelial cell division phenotypes - Lázaro-Diéguez, Francisco (The Rockefeller University Press, 2013)
Columnar epithelia establish their luminal domains and their mitotic spindles parallel to the basal surface and undergo symmetric cell divisions in which the cleavage furrow bisects the apical domain. Hepatocyte lumina interrupt the lateral domain of neighboring cells perpendicular to two basal domains and their cleavage furrow rarely bifurcates the luminal domains. We determine that the serine/threonine kinase Par1b defines lumen position in concert with the position of the astral microtubule anchoring complex LGN–NuMA to yield the distinct epithelial division phenotypes. Par1b signaling via the extracellular matrix (ECM) in polarizing cells determined RhoA/Rho-kinase activity at cell–cell contact sites. Columnar MDCK and Par1b-depleted hepatocytic HepG2 cells featured high RhoA activity that correlated with robust LGN–NuMA recruitment to the metaphase cortex, spindle alignment with the substratum, and columnar organization. Reduced RhoA activity at the metaphase cortex in HepG2 cells and Par1b-overexpressing MDCK cells correlated with a single or no LGN–NuMA crescent, tilted spindles, and the development of lateral lumen polarity.